Filsafat Komunikasi dalam Makrokosmos - Setiawan, Daryanto (JURNAL SIMBOLIKA: Research and Learning in Communication Study, 2019)
The flow of behaviorism is a meritorious flow in the emergence of communication science. Behaviorism is a derivation of positivism that seeks to independent science from philosophy with material objects and formal objects respectively. Thanks to the support of behaviorism and positivism, communication becomes an independent science from philosophy. Communication philosophy is a science that examines fundamentally about the science of communication from its history, its theories, its methods, the methodological principles used, to all matters related to the scope of communication. Whereas macrocosm is a science that discusses the whole universe. There is a fundamental difference about nature between the views of Western philosophy and the views of Islamic philosophy. In the view of Western philosophy, nature happens by itself (by nature). While in the view of Islamic philosophy, nature occurs because there is what makes God. This paper explains that it turns out that the universe, both biotic (plants, animals, humans) and abiotics (earth, water, air, and sunlight) can all communicate. The communication of this nature is explained through scientific research and reinforced by the Qur'an and Hadith.